Is red cell distribution width a prognostic factor in patients with breast cancer? A meta-analysis - Yin, Jun-Ming; Zhu, Ke-Peng; Guo, Zhi-Wei; Yi, Wen; He, Ying; Du, Guo-Cheng (Frontiers in Surgery, 2023)
Purpose The current study aimed to investigate whether red blood cell distribution width (RDW) can predict the prognosis of patients with breast cancer (BC). Methods We searched four databases, including PubMed, Embase, Cochrane Library databases, and CNKI, from inception to Jun 13, 2022. The primary outcome was overall survival (OS), and the secondary outcome was disease-free survival (DFS). A subgroup analysis was conducted based on different treatments. This meta-analysis was performed with RevMan 5.3 (The Cochrane Collaboration, London, United Kingdom). Results A total of seven studies including 4884 BC patients were identified. The high RDW group had a larger tumor size (OR=2.12, 95% CI=1.67 to 2.68, P<0.01), higher proportions of advanced stage tumors (OR=1.77, 95% CI=1.38 to 2.27, P<0.01), more lymph node metastases (OR=2.00, 95% CI=1.58 to 2.51, P<0.01) and lower HER-2 expression (OR=0.76, 95% CI=0.61 to 0.95, P=0.02). For prognosis, after pooling all the data, we found that the high RDW group was associated with worse OS (HR=2.12, 95% CI=1.47 to 3.08, P<0.01) and DFS (HR=1.77, 95% CI=1.32 to 2.37, P<0.01). The subgroup analysis found that RDW had prognostic significance but only for surgery-only patients (HR=2.41, 95% CI=1.67 to 3.49, P<0.01). Conclusion High RDW was associated with worse OS and DFS. Therefore, RDW was a simple predictive factor for the prognosis of BC patients.